Rethinking Emerging Land Markets in Rapidly Growing Southern African Cities: The Political Economy of Urban Land Markets in Africa Examples from Kenya - Robert, Dr. Atambo (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
This paper seeks to explore the dynamics of power and the urban land market; how do existing property markets work in growing African cities in reference to Urban Land Markets in Africa (ULMA), who are the market players and how do they shape the power dynamics of the market.